1993
DOI: 10.1038/bjc.1993.452
|View full text |Cite
|
Sign up to set email alerts
|

Changes in subcellular doxorubicin distribution and cellular accumulation alone can largely account for doxorubicin resistance in SW-1573 lung cancer and MCF-7 breast cancer multidrug resistant tumour cells

Abstract: Summary Doxorubicin accumulation defects in multidrug reistant tumour cells are generally small in comparison to the resistance factors. Therefore additional mechanisms must be operative. In this paper we show by a quantitative approach that doxorubicin resistance in several P-glycoprotein-positive non-small cell lung cancer and breast cancer multidrug resistant cell lines can be explained by a summation of accumulation defect and alterations in the efficacy of the drug once present in the cell. This altera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 30 publications
2
45
0
Order By: Relevance
“…The sequestration of anthracyclines in cytoplasmic structures/vesicles has been described in several drug-resistant cell lines and has been associated with the expression of P-gp, MRP1, and/or MVP (32)(33)(34)(35)(36)(37)(38)(39)(40). However, much is still unclear about the sequestration process and its role in MDR.…”
Section: Discussionmentioning
confidence: 99%
“…The sequestration of anthracyclines in cytoplasmic structures/vesicles has been described in several drug-resistant cell lines and has been associated with the expression of P-gp, MRP1, and/or MVP (32)(33)(34)(35)(36)(37)(38)(39)(40). However, much is still unclear about the sequestration process and its role in MDR.…”
Section: Discussionmentioning
confidence: 99%
“…The shift in the ratio nuclear drug/cytoplasmic drug has been reported to be related to resistance to doxorubicin (2.8-3.6 in sensitive cells vs. 0.1-0.4 in cells with 70-fold higher level of resistance) (Schurrhuis et al, 1993). Biophysical studies (Frezard and Garnier-Suillerot, 1991) demonstrated that the intercalation between the base pairs of DNA induced the partial quenching of DOX fluorescence.…”
Section: Intracellular Accumulation and Distribution Of Dox In Wild Tmentioning
confidence: 99%
“…One possible explanation would involve increased plasma membrane traffic and endosomal compartment as defined by endosomal number, volume and membrane area (Sehested et al, 1987). Alternatively, subcellular compartmentalization, such as a shift of ADR from the nucleus to the cytoplasm (Schuurhuis et al, 1993), may be implied, since ADR in the cytoplasm is rapidly excreted whereas it remains for a long time in the nucleus (Schuurhuis et al, 1993).…”
Section: Discussionmentioning
confidence: 99%